The relationship of a healthy diet with the level of productivity among office workers - Devin Mahendika; Vaulinne Basyir; Lumastari Ajeng Wijayanti; Rika Amran; Ngurah Mahendra Dinatha; Ropitasari Ropitasari (PT. Anagata Sembagi Education, 2025)
This study aims to explore the relationship between a healthy diet and the level of work productivity among office workers. With increasing awareness of the importance of a nutritionally balanced diet, this study examines how a diet that includes proper intake of nutrients, such as iron, relates to worker performance. Data obtained from 210 respondents showed that workers who eat a healthy diet tend to have higher work productivity compared to those who do not maintain a good diet. The study also highlighted the importance of workplace health support in improving productivity, with workers who felt supported by company policies reporting lower levels of fatigue and stress. Based on these findings, companies are advised to introduce policies that support healthy eating and overall well-being in order to improve workers ' productivity and quality of life.